Lupus vulgaris in a child following BCG immunization - Kokcam, Ibrahim; Kose, Ahmet; Yekeler, Hayrettin; Doymaz, M. Ziya (My University, 2001)
A three year old girl presented with lupus vulgaris of the upper arm, which appeared 1 month after BCG immunization. The diagnosis was confirmed by polymerase chain reaction after histology and culture were negative for mycobacteria. Complete healing followed 6 months of oral isoniazid.
Keywords: Cutaneous tuberculosis; Mycobacterium bovis; Polymerase chain reaction